Altered Fibrinolysis in DVT: Influence of Site of Sampling - Han, P; Koay, E S C; Tsakok, M; Aw, T C; Wong, L Y; Pradhan, M (Thrombosis and Haemostasis, 1988)
Alteration of the fibrinolytic system is considered to be important in the development of deep venous thrombosis (DVT). Using specific assays for tissue plasminogen activator (t-PA) activity, t-PA inhibitor (PAI) and t-PA antigen, we measured these activities in 16 women who developed DVT during their pregnancies. A group of 24 healthy females of comparable age was studied as controls. PAI was increased in 87% of these patients compared to the healthy controls. In some of these patients a defect in release of t-PA from vascular endothelium was found as well. The site at which blood was sampled for analysis appeared to be an important criterion in the ex vivo assessment of functional t-PA reserve and PAI levels, though relatively less so for the latter measurement. The unaffected lower limbs, relative to the unaffected upper limbs, showed an increase in PAI and a demonstrable decrease in t-PA release, both representing increased risk factors for rethrombosis. The affected lower limbs showed similar but more accentuated changes in these parameters.
Keywords: Altered fibrinolysis; Deep vein thrombosis; Sampling site